Feasibility of radiofrequency ablation as an alternative to surgical intervention in patients with huge multiloculated pyogenic liver abscesses: A retrospective cohort study. Issue 49 (December 2016) - Ke, Shan; Ding, Xue-Mei; Gao, Jun; Wang, Shao-Hong; Kong, Jian; Xu, Li; Sun, Wen-Bing
Abstract : Abstract: This retrospective cohort study investigated the feasibility of radiofrequency (RF) ablation as an alternative to surgical intervention in patients with huge multiloculated pyogenic liver abscesses (PLAs). From August 2010 to April 2016, 83 patients with PLA were admitted to Beijing Chao-Yang Hospital, China. Four of these patients had huge multiloculated PLAs and underwent RF ablation plus antibiotics. The inclusion criteria for RF ablation were as follows: multiloculated PLA confirmed by computed tomography (CT) or magnetic resonance imaging (MRI), widest diameter of the PLA ≥5 cm, failure to respond to or not suitable to treatment with percutaneous drainage (PD), and patient refusal of surgery. The safety and effectiveness of RF ablation were initially assessed. All patients were commenced on antibiotics on admission to our hospital. CT-guided percutaneous catheter drainage was attempted in one patient but was unsuccessful. The main organism isolated from cultures of these patients' blood or abscess samples was Klebsiella pneumoniae (3/4). RF ablation was performed as soon as eligibility according to the above criteria was established. RF ablation was technically successful in all 4 study patients, all PLAs being completely eradicated. The median duration of fever after RF ablation was 4.5 days. No abscesses recurred; thus, this strategy for managing PLA was 100% successful (4/4). No procedure-related deaths or major complications occurred. One patient had an asymptomatic right pleural effusion that resolved with conservative treatment including albumin infusion and diuretics. Our preliminary data indicate that RF ablation is a safe, feasible, and effective treatment for huge multiloculated PLAs. It should be considered as an alternative treatment for patients who fail to respond to or not suitable for PD plus antibiotics and refuse surgical intervention.